Guía teórico - práctica de acompañamiento terapéutico en niños con trastornos generalizados del desarrollo (Autismo) - Ojeda Briceño, Rocío (2008)
Who believe that we perform as nurses for children with pervasive developmental disorders, extreme problems facing education (socialization, communication, contact, etc.) Because the difficulty is that we lack the knowledge to deal with the education of persons with autism, many times we do not understand what they want, how they arrive at them, and tell them that we are with them but we feel powerless against the denial of their contact to our reality right now is where we face problems of how play the correct work of a therapist, especially because sometimes we do not know if what we are doing or better and this causes uncertainty as a therapist, but in my case I can say that the only sign that all is well is when autistic children are happy.